2020
DOI: 10.5009/gnl19201
|View full text |Cite
|
Sign up to set email alerts
|

Potential Strategies in the Prevention of Nonsteroidal Anti-inflammatory Drugs-Associated Adverse Effects in the Lower Gastrointestinal Tract

Abstract: With the increasing use of nonsteroidal anti-inflammatory drugs (NSAIDs), the incidence of lower gastrointestinal (GI) complications is expected to increase. However, unlike upper GI complications, the burden, pathogenesis, prevention and treatment of NSAID-associated lower GI complications remain unclear. To date, no cost-effective and safe protective agent has been developed that can completely prevent or treat NSAID-related lower GI injuries. Selective COX-2 inhibitors, misoprostol, intestinal microbiota mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 93 publications
0
17
2
2
Order By: Relevance
“…The NSAIDs that are currently available can be classified into two main families: Non-selective NSAIDs (nsNSAIDs) and selective COX-2 inhibitors (coxibs). According to their half-lives, nsNSAIDs can be classified further into two groups: Those with a short half-life (<6 h), including ibuprofen, and those with longer half-lives, including naproxen (19). Ibuprofen and naproxen are commonly used for dysmenorrhea in patients with adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…The NSAIDs that are currently available can be classified into two main families: Non-selective NSAIDs (nsNSAIDs) and selective COX-2 inhibitors (coxibs). According to their half-lives, nsNSAIDs can be classified further into two groups: Those with a short half-life (<6 h), including ibuprofen, and those with longer half-lives, including naproxen (19). Ibuprofen and naproxen are commonly used for dysmenorrhea in patients with adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…Selective COX-2 inhibitors have satisfactory anti-inflammatory and analgesic effects, but they can also cause many adverse reactions, such as gastrointestinal events and cardiovascular disease [ 42–45 ]. Rofecoxib was withdrawn from the market in 2004 due to its significant gastrointestinal reactions and cardiovascular toxicity [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from several laboratories indicate that NO-NSAIDs may be effective in many diseases, including cardiovascular [153], rheumatological [147,154] and pulmonary diseases [152], Alzheimer's disease [155] and cancer [150,156]. Numerous in vitro and animal studies have confirmed the enhanced safety profile of NO-NSAIDs in terms of anti-inflammatory efficacy, gastrointestinal and cardiovascular tolerance, and even heart protection compared to their NSAID parents, although there are also reports of severe side effects [157][158][159][160][161]. An excellent example of such a course of research is the research on the hybrid NO and aspirin (ASA) developed by NiCox in the form of three different isomers (NCX 4040, NCX 4016 and NCX 4012 as para-, meta-, and ortoisomers, (Figure 9).…”
Section: No As a Prodrugmentioning
confidence: 99%